2021
DOI: 10.1364/oe.431974
|View full text |Cite
|
Sign up to set email alerts
|

Generation of structured coherent extreme ultraviolet beams from an MgO crystal

Abstract: Short wavelength high-harmonic sources are undergoing intense development for applications in spectroscopy and microscopy. Despite recent progress in peak and average power, spatial control over coherent extreme ultraviolet (XUV) beams remains a formidable challenge due to the lack of suitable optical elements for beam shaping and control. Here we demonstrate a robust and precise approach that structures XUV high-order harmonics in space as they are emitted from a nanostructured MgO crystal. Our demonstration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Hence, we clearly demonstrate control of electron motion for VUV energies around 20 eV. This is important because these energies are within the range of highharmonics generated from solids where one can harness the surface structure that can be added to solids to focus the VUV light down to the 100 nm scale [37].…”
Section: B Control Of Direction Of Electron Ionization With Vuv+ir Pu...mentioning
confidence: 73%
See 1 more Smart Citation
“…Hence, we clearly demonstrate control of electron motion for VUV energies around 20 eV. This is important because these energies are within the range of highharmonics generated from solids where one can harness the surface structure that can be added to solids to focus the VUV light down to the 100 nm scale [37].…”
Section: B Control Of Direction Of Electron Ionization With Vuv+ir Pu...mentioning
confidence: 73%
“…Using high harmonic generation, it will be possible in the future to generate a focused down to roughly 100 nm VUV light spring from an OAM IR laser field. Indeed, it was recently reported that roughly 12 eV VUV beams were generated by high harmonics from the MgO solid focused down to 100 nm [37]. The circular IR laser beam will be obtained from the fundamental IR laser field as well.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we clearly demonstrate control of electron motion for VUV energies around 20 eV. This is important because these energies are within the range of high harmonics generated from solids where one can harness the surface structure that can be added to solids to focus the VUV light down to the 100 nm scale [37].…”
Section: B Control Of the Direction Of Electron Ionization With Vuv+i...mentioning
confidence: 74%
“…Using high harmonic generation, it will be possible in the future to generate a focused down to roughly 100 nm VUV light spring from an OAM IR laser field. Indeed, it was recently reported that roughly 12 eV VUV beams were generated by high harmonics from the MgO solid focused down to 100 nm [37]. The circular IR laser beam will be FIG.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of solid-state platforms is the ability to form nanostructured systems which provide control over the amplitude, phase, and polarization of the light produced through the nonlinear optical conversion process, , with great significance for the development of novel nanophotonic systems. Recently, there has been a significant effort to develop metasurfaces that can tailor the polarization of light in nonlinear optical processes, especially for chiral light applications, since CPL is useful in a variety of applications in molecular biology, telecommunications, quantum encryption, and analytical chemistry. Unfortunately, since such metasurfaces depend on resonant structures, their optical properties (including the wavelength of operation, NOC efficiency, and light polarization) cannot be tailored dynamically as they are tied to the metasurface geometry and material properties of the system.…”
Section: Introductionmentioning
confidence: 99%